2005
DOI: 10.1074/jbc.m408587200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensing Receptor Gene Transcription Is Up-regulated by the Proinflammatory Cytokine, Interleukin-1β

Abstract: The calcium-sensing receptor (CASR) in parathyroid, thyroid, and kidney is essential for calcium homeostasis. Hypocalcemia is common in critically ill patients having increased circulating proinflammatory cytokines, although the causes are unknown. We hypothesized that the cytokines increase CASR expression and reduce the set point for parathyroid hormone suppression by extracellular calcium, leading to hypocalcemia and hypoparathyroidism. Here, we show in vivo in the rat that parathyroid, thyroid, and kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 48 publications
2
62
1
Order By: Relevance
“…We showed in vivo in the rat that parathyroid, thyroid, and kidney CASR mRNA and protein increased after intraperitoneal injection of IL-1␤ (19). This was associated with decreased circulating PTH, 1,25-dihydroxyvitamin D (1,25(OH) 2 D), and calcium.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We showed in vivo in the rat that parathyroid, thyroid, and kidney CASR mRNA and protein increased after intraperitoneal injection of IL-1␤ (19). This was associated with decreased circulating PTH, 1,25-dihydroxyvitamin D (1,25(OH) 2 D), and calcium.…”
mentioning
confidence: 90%
“…The CASR gene has two promoters (P1 and P2) yielding alternative transcripts containing either exon 1A or exon 1B 5Ј-untranslated region sequences that splice to exon 2 containing the ATG translation start codon (20 -22). We demonstrated that both the CASR gene promoters have functional B elements that mediate up-regulation by IL-1␤ (19).…”
mentioning
confidence: 99%
“…This observation, together with the finding that these agents significantly reduced cyclin D1 expression, provided additional evidence for the anti-proliferative role of CaR activation in parathyroid cells. The interaction between the NF-kB pathway and CaR signaling has recently been demonstrated in animal models, in which the induction of CaR expression by interleukin-1b was found to be mediated by the activation of the NF-kB pathway (Canaff & Hendy 2005).…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…CASR expression in the cell membrane is controlled by two alternative promoters (P1 and P2), located before either exon 1A or exon 1B of the CASR gene. They encode the same CASR protein and their functional differences are still unknown (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%